Enhancing organizational performance through effective leadership and communication - Bajrami, Halil; Lekaj, Fadil; Shala, Venet; Bajrami, Blerona; Bytyqi, Shaip (Edelweiss Applied Science and Technology, 2024)
This empirical paper aims to explore the concept of leadership in organizations and analyze its role and impact on organizational success. Leadership is a key aspect for the development and performance of organizations in a diverse and competitive environment. Referring to the literature and various studies, this paper aims to shed light on the qualities and behaviors that characterize successful business leaders, as well as to identify their strategies and practices used to influence their team towards achieving organizational objectives.Through an in-depth analysis of the literature and studies conducted in the field of leadership and business, the main qualities of successful business leaders will be examined, such as strategic vision, integrity, the ability to make wise decisions, the ability to communicate and inspire, as well as the ability to develop the team and encourage innovation. By understanding the role and impact of leadership, organizations can develop appropriate strategies and practices to improve performance and achieve long-term success in a changing and challenging environment.